COMPARATIVE STUDY OF CULTURE AND PCR FOR DETECTION OF CARRIERS OF STREPTOCOCCUS EQUI IN NATURALLY INFECTED MULES IN PAKISTAN - M. Ijaz; M. S. Khan; M. A. Khan; A. Maqbool; M. M. Ali; A. Rehman; K. Mehmood; M. H. Saleem; M. Z. Shabbir (Journal of Animal and Plant Sciences, 2012)
This is the first report of carrier of Streptococcus equi (S. equi) in naturally infected mules in Pakistan. A total of 20 mules (10 <2 year and 10 of 2-5 years) infected with strangles that remained positive after one week of recovery were selected and monitored for 12 weeks. After the end of 2nd week all mules < 2 years of age were positive but at the end of 3rd to 6th weeks there remained 7, 3, 1 and zero out of 10 on the basis of culture but through PCR, at the end of the 5th week all mules < 2 years of age were positive, but at the end of 6th to 10th weeks there remained 9, 7, 3, 2 and zero out of 10. Similarly the carrier status in 2 and 5 year old mules was also evaluated. All mules were positive up to the 2nd week but at the end of 3rd to 7th weeks there were 6, 4, 2, 1 and zero out of 10 mules on the basis of culture while through PCR, all mules were positive up to 5th week but at the end of 6th to 10th weeks there were 8, 5, 2, 1 and zero. It is concluded that do not mix recovered mules from strangles with healthy equines at least for 9 weeks because the recovered mules remain carriers for prolonged period of time.
Keywords: Mules; PCR; Streptococcus equi; carrier; Pakistan.